Effects of stratification on chloramine decay in distribution system service reservoirs - Fisher, I.; Sathasivan, Arumugam; Chuo, P.; Kastl, G. (Elsevier Science Ltd, 2009)
Water quality in chloraminated distribution systems is affected by microbial activity, particularly due to nitrifiers that accelerate chloramine decay. In summer, continuous thermal stratification increases retention time and lowers chloramine residual in some parts of a system service reservoir (tank), relative to fully mixed conditions. According to temperature and chemical indicators, cooling in winter destratifies these reservoirs naturally. Traditional (chemical) indicators of nitrification also suggest that destratification occurs with respect to microbiological activity. In contrast, the microbial decay factor (Fm) method, which separates microbiological and chemical decay in bulk water, identifies strong microbial stratification, even in winter. Fm can also be used to predict the exacerbated loss of chloramine residual in the following summer, which enables early intervention by system managers to minimise such loss, and so maintain an adequate residual through the distribution system.